PERBANDINGAN HUKUM KEDUDUKAN AHLI WARIS PENGGANTI BERDASARKAN HUKUM KEWARISAN ISLAM DENGAN HUKUM KEWARISAN MENURUT KUHPERDATA - Peni Rinda Listyawati; Wa Dazriani (UNISSULA, 2015)
Indonesia imposed three legal systems, namely western law, Islamic law and customary law, each of which has its own arrangements, including inheritance arrangements, in particular on the provisions of the replacement heirs. The legal arrangement of inheritance regarding the provisions of the replacement heirs there are similarities and differences of position which are set by each legal system, especially between Islamic inheritance law and inheritance law according to the Civil Code. The research method used by the method of juridical normative in the form of theory, concept and idea about the comparison of surrogate heirs between Islamic inheritance law with the law of inheritance according to the Civil Code. In the research conducted, the authors obtained the result that the position of the surrogate heirs in the inheritance of Islam formulated tentatively in Article 185 paragraph (1) KHI and in the Civil Code formulated in Article 841-848 Civil Code. Differences of substitute heirs according to the Law of Inheritance of Islam with the Law of Inheritance according to the Civil Code one of which is the right that the substituted heirs obtain is not necessarily the same as the right of the person to be replaced, nor shall it be exceeded from the part of the heir equal to that which is replaced, but may be reduced. According to the inheritance law of the Civil Code of the section to be obtained the heirs who replaced his father’s position exactly the same as the part that should have been his father if his father still lives from the heir.